New species of Cryptophleps Lichtwardt (Diptera: Dolichopodidae) with a key to the Afrotropical and Palaearctic species of the genus - Grichanov, Igor Ya. (Zootaxa, 2015)
Two new species, Cryptophleps namibica sp. nov., from Namibia and C. buttikeri sp. nov., from Saudi Arabia are described. The following new combinations are proposed: Cryptophleps izia (Negrobov, 1973) (Asyndetus), comb. nov. (Central Asia), Cryptophleps minuta (Negrobov & Shamshev, 1986) (Asyndetus), comb. nov. (Far Eastern Asia) and Cryptophleps vivida (Negrobov & Shamshev, 1986) (Asyndetus), comb. nov. (Far Eastern Asia). The systematic positions of species of Cryptophleps are discussed. An identification key to Afrotropical and Palaearctic species is provided.